Kinetic analysis using electromyography against yeop chagi in taekwondo poomsae athletes state university of jakarta - Harsono, Priyaka Irfan Astama; Sukur, Abdul; Fachrezzy, Fahmy (Gladi : Jurnal Ilmu Keolahragaan, 2023)
This study aims to provide information on how UNJ taekwondo Poomsae athletes can gain muscle strength in the Yeop Chagi kick using electromyography. This thesis uses the true experiment method. The research for this thesis was conducted at the Flats of the Faculty of Sports Science, State University of Jakarta, Rawamangun, East Jakarta. The population in this study were all 8 Taekwondo Poomsae athletes, between 4 males and 4 females. From the results of data analysis, descriptions, examiners of research results, and discussion, conclusions can be drawn, namely, Kinetic Analysis Using Electromyography Against Yeop Chagi in Taekwondo Poomsae Athletes, State University of Jakarta. Based on the t-test, Pre-Test and Post-Test electromyography aim to determine whether there is an increase in the score. The study’s conclusion was declared significant if t count > t table at a significance level of 5% and p-value < 0.05. Based on the table above, we obtained an average of 40.32. It was also found that the t count > t table at the level of 5% = -4.528 to 4.528 (4.528 > 2.023) and had a p-value of <0.05, which means that it can be concluded that there was a significant increase in the result score of the Electromyography group. The t-test Pre-Test and Post-Test Yeop Chagi aims to determine whether there is an increase in the score. The study’s conclusion was. Declared significant if it count > t table at a significance level of 5% and p-value <0.05. Based on the table above, we obtained an average of 1.378. It was also found that the t-count > table at the level of 5% = -8.291 to 8.291 (8.291 > 2.023) and had a p-value of <0.05, which means that it can be concluded that there was a significant increase in the result score of the Yeop Chagi group.